Fighting forest crime and promoting prudent banking for sustainable forest management: the anti money laundering approach - Setiono, B.; Husein, Y. (Center for International Forestry Research, 2005)
If illegal logging was a crime involving only poor forest-dependent people, truck drivers or underpaid forest rangers, it would not be difficult to stop. With involvement of financiers of illegal logging, known as cukong, legal timber industries, and government officers, illegal logging becomes a complex problem not only for Indonesia, but also for the international forestry community. The current forestry law enforcement approach fails to capture the masterminds of illegal logging. However, the money laundering law enforcement approach which ‘follows the money’ provides an important option to deal with the masterminds of illegal logging. This new approach requires banks and other financial service providers to be more active and prudent in dealing with financial transactions related to their customers. Bank customers could include financiers of illegal logging, timber industries, law enforcement and government officers. Overall, proper implementation of the anti money laundering regime should provide opportunities for promoting prudent banking practices and sustainable forest management, and for curtailing forestry crimes.